National Education Policy 2020 and Gender Inclusiveness - Dr. Seema Ghanghas, Dr. Waseem Ahmad Khan, Prabha Singh Parihar (Journal of Informatics Education and Research, 2024)
Disparities between men and women have persisted in society for a long time. Even though various measures have been taken the relevance of school textbooks and the curriculum that students are subjected in terms of encouraging gender-exclusivity cannot be overstated in order to promote gender equality and the removal of current gender norms. The formation of gender stereotypes in youngsters is aided by every aspect of our education, including textbooks, stories, images, and examples. An overview of the New Policy 2020 was used to conduct a comparative analysis of Indian educational institutions in order to identify the flaws in our system, suggesting that the our nation still has a long way to go in achieving SDGs 4 and 5. The researchers have also proposed various approaches and prospective solutions aimed at revolutionising India's educational landscape and promoting academic equity and inclusivity. In addition, this study examines the Education 2030 Framework’s recommendations for 'Refurbishing Public Education in India with an intent to make It Gender-Inclusive,' and it proposes a multi-sectoral strategy to empower women as a prerequisite.